Inside Jesuit Classrooms: Students’ Notebooks from the Austrian Province of the Late Sixteenth Century - Förköli, Gábor (Journal of Jesuit studies, 2024)
In the sphere of education, early modern Jesuit documents prescribed a large variety of didactical methods. As a result, Jesuit education was perceived as facilitating a dialogue between traditional Scholasticism and humanism or scientific progress. However, complaints from the first half-century of the order indicate that Jesuit schools fell short in terms of their compliance with prescriptive regulations. Indeed, non-Jesuit scholars often considered the order to be conservative traducers of Renaissance scholarship. To assess these contradictory evaluations, this article proposes to scrutinize manuscripts produced by students during their philosophical studies at the colleges of Vienna, Olomouc, and Graz, falling within the timeframe of c. 1580–90. Here, I look to argue that, even before the universal presence of comprehensive Jesuit textbooks, the teaching of philosophy was not only surprisingly unified within the province but new scientific and scholarly developments, including the Gregorian Reform and the debates around Copernican views, were also presented in the Jesuit classroom.